The Portuguese version of the Personality Inventory for the DSM-5 in a community and a clinical sample - Pires, R.; Sousa Ferreira, A.; Gonçalves, B.; Henriques-Calado, J.; Paulino, M. (Personality and Mental Health, 2019)
The Personality Inventory for DSM-5 (PID-5) measures the maladaptive traits of the model for personality and its disorders, as proposed in section III of the DSM-5. The current study aimed to examine whether the Portuguese PID-5 distinguished non-clinical participants (N = 1223, Mage = 36.73, standard deviation = 15.72) from clinical participants (N = 202, Mage = 43.82, standard deviation = 11.33) with respect to dysfunctional personality traits and to explore the PID-5 factor structure in both samples. The PID-5 scale medians were higher in the clinical sample than in the community sample. All analyses were statistically significant (p ≤ 0.001) with medium size effects. In the community sample, a five-factor structure emerged, and the factors resembled the PID-5 domains. However, in the clinical sample, a four-factor structure was retained, in which the Psychoticism domain did not clearly emerge. The composition of the clinical sample along with its small size may account for these unexpected results. Overall, the results provide evidence of the PID-5's ability to distinguish between psychiatric and community individuals and of the model's structural similarity in community samples, across studies and nationalities. More research is required to understand the Portuguese PID-5 structure in clinical samples.